Studying Dynamics of Human Information Gathering Behaviors Using Social Robots - Eshed, Matan; Epstein, Matan; Zohar, Ada H.; Gordon, Goren (Frontiers in Psychology, 2021)
A novel social interaction is a dynamic process, in which participants adapt to, react to and engage with their social partners. To facilitate such interactions, people gather information relating to the social context and structure of the situation. The current study aimed to deepen the understanding of the psychological determinants of behavior in a novel social interaction. Three social robots and the participant interacted non-verbally according to a pre-programmed "relationship matrix" that dictated who favored whom. Participants' gaze was tracked during the interaction and, using Bayesian inference models, resulted in a measure of participants' social information-gathering behaviors. Our results reveal the dynamics in a novel environment, wherein information-gathering behavior is initially predicted by psychological inflexibility and then, towards the end of the interaction, predicted by curiosity. These results highlight the utility of using social robots in behavioral experiments.